2020
DOI: 10.1007/s00418-020-01866-w
|View full text |Cite
|
Sign up to set email alerts
|

Genes regulating hormone stimulus and response to protein signaling revealed differential expression pattern during porcine oocyte in vitro maturation, confirmed by lipid concentration

Abstract: Genes influencing oocyte maturation may be valuable for predicting their developmental potential, as well as discerning the mechanistic pathways regulating oocyte development. In the presented research microarray gene expression analysis of immature and in vitro matured porcine oocytes was performed. Two groups of oocytes were compared in the study: before (3 × n = 50) and after in vitro maturation (3 × n = 50). The selection of viable oocytes was performed using the brilliant cresyl blue (BCB) test. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Non-apoptotic epithelial cells are dedifferentiated to mesenchymal cells as “seeds” for subsequent lactation cycles. The transforming growth factor beta receptor 3 ( TGFBR3 ) and WW domain containing transcription regulator 1 ( WWTR1 ) induce the transformation of epithelial cells into mesenchymal cells [ 80 , 81 ]. Additionally, the bone morphogenetic protein receptor type 1A ( BMPR1A ) plays an important role in maintaining the undifferentiated state of mammary epithelial cells [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-apoptotic epithelial cells are dedifferentiated to mesenchymal cells as “seeds” for subsequent lactation cycles. The transforming growth factor beta receptor 3 ( TGFBR3 ) and WW domain containing transcription regulator 1 ( WWTR1 ) induce the transformation of epithelial cells into mesenchymal cells [ 80 , 81 ]. Additionally, the bone morphogenetic protein receptor type 1A ( BMPR1A ) plays an important role in maintaining the undifferentiated state of mammary epithelial cells [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 and Fig. S 2 ) [ 79 , 80 ]. The above molecular mechanisms maintain the lactation potential of the mammary gland and guarantee the next lactation cycle.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with existing research results; hence, we further classified DEG. The results showed that the genes are mainly enriched in the PI3K signaling pathway and have an impact on IVM of ovine oocytes through the following five aspects: (1) Oocyte maturation, the overexpression of genes such as CCND2, PDGFC, IFRD1, H2AFZ, INHBA, CD200, and RPS26 indicated that both groups of oocytes had undergone IVM [19][20][21][22][23][24][25]. However, in the experimental group, the expression levels of TNFAIP6 related to cumulus cell proliferation [13], SPP1 related to in vitro development of oocytes [26], RUNX2 related to follicular development [27], and C1QB related to embryonic development were downregulated [28], indicating that ZEN may inhibit the process of oocyte maturation by influencing these genes.…”
Section: Discussionmentioning
confidence: 99%